Practical Models of Waqf Fundraising: Study on The Waqf-Based Pesantrens in Indonesia - Muhammad Shulthoni; Norma Md Saad; Muhammad Irwan Ariffin; Saim Kayadibi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
This paper aims to explain waqf fundraising and its communication among the waqf institutions of pesantrens in Indonesia. The study focuses on the application of innovative waqf fundraising and communication strategies in three waqf-based pesantrens, namely Pondok Darussalam Gontor, Darunnajah, and Tazakka. The primary data are obtained through semi-structured interviews, while the secondary data are collected through observations and document reviews. Both data provide important and useful insights into understanding the waqf fundraising and communication approaches in these waqf institutions. In addition, thematic analysis is utilised in this study to analyse the application of the waqf fundraising models that contribute significantly to the development of waqf in the sampled pesantrens. The results of the study suggest that different types of waqf institutions apply different waqf fundraising methods. Darussalam Gontor and Darunnajah waqf institutions have a similar propensity for using traditional waqf fundraising approaches in which mobilisation and collection of waqf utilise retail and partnership fundraising techniques. While, Tazakka waqf institution applies both modern (market-oriented) and traditional waqf fundraising methods, in which retail, partnership, and crowd (jamā’i) fundraising techniques are used for mobilisation of their waqf. In relation to communication, these three waqf institutions utilise the same methods, that is, individual and community-oriented communications for linking their waqf programmes and activities. These methods of communication are set up to build and manage stronger relationships with key wāqifs. Finally, the study found that these waqf institutions have implemented simple communication approaches and utilised an effective fundraising method in creating and maintaining individual and institutional contributions.